PENERAPAN METODE DRILL DENGAN MEDIA KARTU PINTAR JAWA (KAPIJA): EFEKTIFITAS DALAM PEMBELAJARAN BAHASA JAWA - Kellyna Cahya Widya; Dwiana Asih Wiranti; Nina Sofiana (Universitas Tribhuwana Tunggadewi, 2024)
The purpose of this study was to determine the application of the drill method combined with Kartu Pintar Jawa (KAPIJA) media in improving student learning outcomes in class V SDN 2 Mantingan in Javanese script learning. The research method used was quantitative with a pre-experimental design involving 42 elementary school students. The results of this study revealed that student learning outcomes were proven to have increased as seen from the average pretest score of 44.4 increasing to 79.6 in the posttest. In addition, the t-test resulted in a 2-Tailed significance value = 0.000, indicating that there was a significant difference between the pretest and posttest results. The results showed that the combination of drill method and KAPIJA media was effective in improving students' understanding of Javanese characters. This combination succeeded in improving students' Javanese script literacy by making learning more interactive and fun.